Comparison of field measurements to predicted reaeration coefficients, k₂, in the application of water quality model, QUAL2E, to a tropical river - Mohamed, Maketab, author; Stednick, John D., advisor; Smith, Freeman M., advisor; Fontane, Darrell G., committee member; Elder, Kelly J., committee member (Colorado State University. Libraries, 2000)
Some of the tools used for watershed management in the last two decades are the computer models for wasteload allocations. QUAL2E, one of the most popular water quality models used for such purposes, was developed by the United States Environmental Protection Agency (USEPA). Therefore it is not surprising that the model mostly has been used and refined in a temperate environment. The question raised is whether the model is applicable in a different climate such as tropical rivers. The null hypothesis (H0) is that the measured reaeration coefficient (k2) for a tropical river will give better results than the predictive equations in QUAL2E since these equations were developed in a temperate environment using temperate climate river variables. QUAL2E uses either the predictive equations within the model or measured reaeration coefficient input. The present study was done on Sg. Selangor River in Malaysia. The results indicate that QUAL2E worked best with measured reaeration coefficient (k2), which gave the lowest standard error (SE = 1.31) for the simulation of water quality using the 7Q10 discharge data, considered as the worst case scenario in water quality modeling. At the same time several predictive equations within QUAL2E (Langbein-Durum (1.29), O'Connor-Dobbins (1.34), Churchill et al. (1.35) and Owens et al. (1.42)) gave better results (lower SE) during calibration and validation using actual low-flow discharge data. At high-flow conditions, the Thackston-Krenkel (SE = 1.45) and the Tsivoglou-Wallace (1.22) predictive equations tended to have the lower standard errors. But these results are suspect since the channel geometry parameters used in the modeling were measured during a low-flow period. The decision of whether to measure specific reaeration coefficients for each river to be modeled or to use the predictive equations depends on the specific needs of the modeler. If accurate results are needed, the modeler would probably need to measure the reaeration coefficients. Otherwise, the four predictive equations within QUAL2E (Langbein-Durum, O'Connor-Dobbins, Churchill et al and Owens et al. equations) would be adequate.
Pages 50, 220, and 253 missing in number only.
Keywords: hydrology; environmental science; hydrologic sciences